Natural Polymers in ihe Development of Floating Drug Delivery Systems: A Review - Ganesh, Kumar; Archana, Dhyani; Preeti, Kothiyal (International Journal of Pharmaceutical and Life Sciences, 2013)
The purpose of writing this review on floating drug delivery systems (FDDS) was to compile the recent literature with special focus on the principal mechanism of floatation to achieve gastric retention . This can be achieved by use of various polymeric substances including natural polymers. These polymers are inexpensive, safe and available in a variety of structures with versatile characteristics. Large number of derivatizable groups, wide range of molecular weights, varying chemical composition gel forming nature of these polymers also provide an exciting opportunities in the fascinating arena of applied polymer science and drug delivery technology. All these characteristics make them suitable candidate for design and fabrication of novel gastroretentive drug delivery systems. Various natural polymers have been investigated worldwide by scientific community for their potential as floating drug delivery systems. The present article highlights various recent efforts and advanced approaches exploiting several natural polymers in this technology. DOI: http://dx.doi.org/10.3329/ijpls.v2i4.17116 International Journal of Pharmaceutical and Life Sciences Volume 2, Issue 4: October 2013; 165-178